Analysis Of Hindu Adolescent Balinese Vocabulary Mastery - I Made Luwih (Kamaya: Jurnal Ilmu Agama, 2021)
Language is a means or tool of communication in a society that functions to express thoughts, feelings, wishes, events, and all human experiences in life to others. The language also could be conveyed through written language. One of them is by composing. Thus, the communication conveyed through written language can be listened to well by the reader. Then, first, we have to master some vocabulary. Several factors cause the communication to not run smoothly due to a lack of vocabulary mastery.